Structural and optical characteristics of erbium doped ternary TeO2-TiO2-Bi2O3 glasses - Baki, S. O.; Tan, L. S.; Kan, C. S.; Halimah, Mohamed Kamari; Mahdi, M. A. (Trans Tech Publications, 2017)
In this work we investigated both structural and optical characteristic of erbium doped ternary TeO2-TiO2-Bi2O3 tellurite oxide based glasses, synthesized via melt-quench method. The X-ray diffraction (XRD) and differential scanning calorimetry (DSC) confirmed its glassy nature and stability. Raman analysis revealed the presence of various coordination state TeO2 network consisting stretching/bending vibrations of Te-O bonds in the [TeO4] trigonal bi-pyramid units and fraction of [TeO3, TeO3+1] trigonal pyramids. From optical absorption measurement both optical band gap and Judd-Ofelt analysis (intensity parameters Ωt (t=2, 4, 6), transition probabilities, and radiative lifetimes of the Er3+ ions) have been performed for both host and doped glasses respectively. Photoluminescence studies for upconversion and near-infrared emissions analysis (under 980 nm excitation at room temperature. Both optical transition mechanism which involved nonradiative energy transfer between Er3+ ions through cross-relaxation and energy migration were also explained in detailed.